Linguistic hybridity between Javanese and Bahasa Indonesia in contemporary Javanese songs - Maryani, Zulisih; Legino, Rafeah; Waijittragum, Pibool (Gelar: Jurnal Seni Budaya, 2025)
This study investigates the phenomenon of linguistic hybridity between Javanese and Bahasa Indonesia in contemporary Javanese songs. It aims to identify the linguistic forms, aesthetic and cultural functions, and the evolving patterns of language use that distinguish traditional from modern song compositions. Using a qualitative descriptive method grounded in a literature-based approach, the research analyses selected Javanese song lyrics that demonstrate hybrid linguistic structures. The findings reveal three major forms of hybridity at the levels of words, phrases, and clauses or sentences. These hybrid forms serve multiple functions: (1) aesthetic, through rhymic and phonetic harmony; (2) expressive, through creative expressions unattainable within a single language; and (3) cultural identity, by reinforcing Javanese characteristics amid the influence of Bahasa Indonesia. Comparison between traditional macapat compositions and contemporary songs highlights a shift from strict monolingual use to flexible bilingual creativity, reflecting an ongoing negotiation of cultural identity in an era of modernisation and globalisation. This study enriches the understanding of how linguistic hybridity contributes to the preservation and evolution of Javanese artistic expression.